Roughness (MANNING) COEFFICIENT VALUE STUDY WITH HEC-RAS SOFTWARE VERSION 4.0 - Ratna Musa; Hanafi Ashad; Trifandy Musafir Wellang (UNDERPASS Journal of Civil Engineering, Applied Sciences, and Technology, 2018)
Swadaya ponds are located in Lamasi District, Luwu Regency, South Sulawesi Province with a total area of ​​384 hectares of ponds. The Swadaya pond drainage system consists of a carrier channel and a discharge channel with water sources for irrigating the pond area obtained from fresh water sources taken from the Central Minanga river and salt water sources taken directly from the sea (Teluk Bone). The simulation was carried out on the Swadaya pond channel in Luwu Regency with Unsteady conditions using the HEC-RAS 4.0 software (Hydrologic Engineering Center-River Analysis System) issued by the US Army Corps of Engineering. What is reviewed with various quantities of Q80 and Qmin annual discharges for upstream Boundary Conditions and for downstream conditions using the influence of tidal changes, this is to find out how big the hydraulic changes are in the Swadaya pond channel. From the simulation for the boundary conditions Q80 and Qmin shows that: The greater the discharge in the upstream channel conditions, the greater the discharge, velocity, and depth of flow in the channel. At high tide, the flow discharge from upstream (Central Minanga River) to the primary carrier channel is smaller than at low tide. Meanwhile, the discharge that enters the secondary channel is greater when the water is in high tide. As for the effect of the Manning coefficient on discharge, time and distance, the smaller the discharge (Qmin = 13.99 m3/s) in upstream conditions, the effect of high tide will be greater and the distance from downstream will be further (s = 2680.64 m) and the greater the discharge (Q80 = 21.37 m3/s) in the upstream, the smaller the influence of the tide and the closer the distance from the downstream (s = 2665.33 m). In order for the availability of water to meet the needs of pond water in the Swadaya pond channel, a trial and error test is carried out on the slope of the secondary and tertiary canals.